Teaching English Vocabulary for A1 Level Pupils - Pakirdinova Sharofat Abdumutalovna; Gulnoza Qahhorova Abduqobil qizi (Journal of Innovation in Education and Social Research, 2023)
This article will highlight the methods and their benefits for teaching English vocabulary to children at A1 level. These methods are very useful in teaching children not only English words but also other languages.